Synchronization of estrus in yearling beef heifers with the MGA®/prostaglandin F2α system: III. timed insemination after 72 hours of estrous detection - Larson, Robert L.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The percentage of heifers conceiving to artificial insemination (AI) following melengestrol acetate/prostaglandin F2"(MGA®/PG) estrous synchronization can be increased by mass insemination of all heifers not showing estrus by 72 h after PG. Inseminating at 12 h after estrus detection all heifers showing estrus within 72 h after PG; then inseminating those not detected in estrus by 72 h after PG as a group increased the proportion of heifers conceiving to AI by 10.8%.
Keywords: Beef; MGA/PG; Heifers; Timed mating; Conception rate